Perancangan Taman Kota sebagai Ruang Terbuka Hijau Berkelanjutan : (Studi Kasus: Taman Mandiri Kota Jayapura) - Hizkia Tonapa Arung; Deasy Widyastomo; Marsal Arung Lamba (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Green Open Space (GOS) plays a strategic role in modern urban planning, serving not only as an ecological element but also as a social, educational, and recreational space that supports the sustainability of urban life. Its presence is a vital necessity in addressing the challenges of urbanization and environmental degradation. This study examines and redesigns Taman Mandiri in Jayapura City as a sustainable urban park capable of accommodating various ecological and social functions. Field observations reveal that the existing condition of the park does not yet meet adequate public facility standards, such as the availability of interaction space, playgrounds, toilets, and parking areas. Through a sustainable landscape design approach, the park is directed to become an inclusive, efficient, and environmentally friendly green open space. The proposed design integrates the use of local vegetation, natural water management systems, and the enhancement of the park’s social functions. It is expected that this design can serve as a model for urban park development in tropical regions facing urbanization pressures and contribute to improving the quality of life in a sustainable manner.